Persepsi Guru Pendidikan Agam Islam Tentang Pembelajaran Berbasis Gender di Madrasah Ibtidaiyah - Chandra, Yudi Ardiansyah; Rikhanah, Rikhanah; Windari, Siska (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to explore the perceptions of Islamic Religious Education (PAI) teachers regarding gender-based learning at MIS Humayroh Labuhanbatu Utara. Using a qualitative approach with a case study design, the research collects data through observations, interviews with teachers and the principal, and document analysis. The findings show that most teachers have a positive view of gender equality in education but face challenges in implementing gender-based teaching practices due to cultural and social norms. While teachers acknowledge the importance of equal opportunities for both male and female students, traditional gender roles often influence their teaching methods. Despite these challenges, classrooms that integrate gender equality show more active participation from both male and female students. This research contributes to the field of Islamic education by providing insights into how teachers perceive and implement gender-based learning, highlighting the importance of gender-sensitive teaching in fostering inclusive and effective learning environments.